What Could Be Future Scenarios?-Lessons from the History of Public Health Surveillance for the Future - Bernard C.K. Choi (AIMS Press, 2015)
This article provides insights into the future based on a review of the past and present of public health surveillance-the ongoing systematic collection, analysis, interpretation, and dissemination of health data for the planning, implementation, and evaluation of public health action. Public health surveillance dates back to the first recorded epidemic in 3180 BC in Egypt. A number of lessons and items of interest are summarised from a review of historical perspectives in the past 5,000 years and the current practice of surveillance. Some future scenarios are presented: exploring new frontiers|enhancing computer technology|improving epidemic investigations|improving data collection, analysis, dissemination and use|building on lessons from the past|building capacity|and enhancing global surveillance. It is concluded that learning from the past, reflecting on the present, and planning for the future can further enhance public health surveillance.